Effects of Storage on Physicochemical Properties and Microbiological Qualities of African Breadfruit-Corn Yoghurt - Ifediba, D.I.; Ozoh, C.N. (European Scientific Journal, ESJ, 2018)
African breadfruit-corn milk was obtained from blend of extracts of African breadfruit (Treculia africana var africana) and sweet corn (Golden cob F1) on 60:40 proportions. The breadfruit-corn milk was fermented to give a yoghurt-like product using inoculums from activated batch of dried starter culture and previously made breadfruit-corn milk. The breadfruit-corn yoghurt was stored in the refrigerator for four weeks, during which changes in physicochemical properties and microbiological qualities were examined weekly against commercial dairy yoghurt. It was found that changes in total solids, pH, titratable acidity, apparent viscosity, syneresis, water holding capacity followed similar trends, except for the whey drainage of the commercial dairy yoghurt which was constant at 0.00. The two yoghurt samples also exhibited similar microbiological changes during the period of study. Thus suggesting that non-dairy yoghurt from African breadfruit-corn milk shared common keeping characteristics with the dairy yoghurt.